2004
DOI: 10.1111/j.1464-410x.2004.04996.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prostate cancer on extended biopsy in patients with high‐grade prostatic intraepithelial neoplasia: a multivariate analysis model

Abstract: DRE. Overall, 49 patients had a transurethral resection of the prostate (TURP). The cancerdetection rate on extended biopsy was correlated with risk factors using the chisquare test and multivariate analysis. RESULTSExtended biopsy detected prostate cancer in 30 of the 83 men (36%), with positive cores in only 20 sextant biopsy sites (67%), in only seven in additional sites (23%), and both in three (10%). Of the 21 patients who had repeat extended biopsy, four (19%) had cancers. There were two carcinomas in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy. Our result also agreed with that of Bostwick et al [2], Abdel-khalek et al [23] and Rosser et al [27], However, it disagreed with studies that revealed lower prostate detection rate (De Nunzio et al [22], Kamoi et al [28] and Epstein & Herawi [29]) and other studies with higher prostate detection rate (Keetch et al [30] and Borboroglu et al [25]). …”
Section: Discussionsupporting
confidence: 36%
“…This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy. Our result also agreed with that of Bostwick et al [2], Abdel-khalek et al [23] and Rosser et al [27], However, it disagreed with studies that revealed lower prostate detection rate (De Nunzio et al [22], Kamoi et al [28] and Epstein & Herawi [29]) and other studies with higher prostate detection rate (Keetch et al [30] and Borboroglu et al [25]). …”
Section: Discussionsupporting
confidence: 36%
“…Among them, analyzing only the studies that included a large number of patients, the mean risk of PCa development among patients with HG–PIN was 24.1% (range: 21.7% to 28.9%) [3133]. In more recent studies, the estimated risk is currently estimated at 18.1% (range: 16.7% to 19.6%) [34, 35, 36]. In the analyzed study, a repeat biopsy was performed in 19 patients with ASAP, and in four of them (21.05%) PCa was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HGPIN on needle biopsy varies from 0.7 to 25% (Table 1), [3][4][5][6][7][8][9][10][11][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] with a mean incidence of 9.55% (median 8.75%). Authors from the WHO Consensus Conference in 2000 also reported on the frequency of HGPIN, particularly on needle biopsy specimens, with a range of 0.8-23.9%.…”
Section: Biopsy Seriesmentioning
confidence: 99%
“…1,2 The incidence of HGPIN on contemporary biopsy series ranges up to 20% with most series reporting an incidence of 2.7-9.5%. [3][4][5][6][7][8][9] Given the increasing number of prostate biopsies performed annually in the United States, the number of men with isolated HGPIN is increasing. To date, there is general disagreement about how to properly follow and treat these men.…”
mentioning
confidence: 99%